Waging War from Remote Cubicles: How Workers Cope with Technologies That Disrupt the Meaning and Morality of Their Work - Rauch, Madeleine; Ansari, Shahzad (Shaz) (Organization Science, 2022)
Technologies are known to alter social structures in the workplace, reconfigure roles and relationships, and disrupt status hierarchies. However, less attention has been given to how an emerging technology disrupts the meaning and moral values that tether people to their work and render it meaningful. To understand how workers respond to such an emerging technology, we undertook an inductive, qualitative study of military personnel working in unmanned aerial vehicles, or drone operations, for the U.S. Air Force. We draw on multiple data sources, including personal diaries kept by personnel involved in drone operations. We identified three characteristics of drone technology: remote-split operations, remote piloting of unmanned vehicles, and interaction through iconic representations. Our analysis suggests that drone technology has revolutionized warfare by (1) creating distanciated intimacy, (2) dissolving traditional spatio-temporal boundaries between work and personal life, and (3) redefining the legal and moral parameters of work. Drone program workers identified with these changes to their working environment in contradictory ways, which evoked emotional ambivalence about right and wrong. However, their organization gave them little help in alleviating their conflicting feelings. We illuminate how workers cope with such ambivalence when a technology transforms the meaning and morality of their work. We extend theory by showing that workers’ responses to a changed working environment as a result of a remote technology are not just based on how the technology changes workers’ tasks, roles, and status but also on how it affects their moral values.